Transdisciplinary Teacher Education - Sue L. T. McGregor (Education Sciences, 2022)
This position paper proposes that teacher education programs should shift from preparing teachers who are consumers and perpetuators of grand narrative knowledge to teachers who are creators and knowers of transdisciplinary (TD) knowledge and perpetuators of a TD narrative. To that end, the Nicolescuian TD methodology, especially epistemology, was introduced as a new grounding for knowledge that can lead to transdisciplinary teacher education. This paper explores what teacher education might look like through a Nicolescuian TD lens with its innovative focus on epistemology—the knowledge required to function in a complex, modern world confronting wicked problems. As this is currently a nascent and untested idea, recommendations for future research are suggested (practice, policy, and theory).